Chitosan alleviates symptoms of Parkinson’s disease by reducing acetate levels, which decreases inflammation and promotes repair of the intestinal barrier and blood–brain barrier - Yinying Wang; Rongsha Chen; Guolin Shi; Xinwei Huang; Ke Li; Ruohua Wang; Xia Cao; Zhongshan Yang; Ninghui Zhao; Jinyuan Yan (Neural Regeneration Research)
Studies have shown that chitosan protects against neurodegenerative diseases. However, the precise mechanism remains poorly understood. In this study, we administered chitosan intragastrically to an MPTP-induced mouse model of Parkinson’s disease and found that it effectively reduced dopamine neuron injury, neurotransmitter dopamine release, and motor symptoms. These neuroprotective effects of chitosan were related to bacterial metabolites, specifically short-chain fatty acids, and chitosan administration altered intestinal microbial diversity and decreased short-chain fatty acid production in the gut. Furthermore, chitosan effectively reduced damage to the intestinal barrier and the blood–brain barrier. Finally, we demonstrated that chitosan improved intestinal barrier function and alleviated inflammation in both the peripheral nervous system and the central nervous system by reducing acetate levels. Based on these findings, we suggest a molecular mechanism by which chitosan decreases inflammation through reducing acetate levels and repairing the intestinal and blood–brain barriers, thereby alleviating symptoms of Parkinson’s disease.